A highly polar phytocomplex involving rutin is responsible for the neuromuscular facilitation caused by Casearia sylvestris (Guaï¿½atonga) - Yoshida, Edson H.; Tribuiani, Natï¿½lia; Foramiglio, Amï¿½ris L.; Foramiglio, Caroline A.; Da Silva Tavares, Renata V.; Bonomini, Tiago J.; Bueno, Paula C. P. [UNESP]; Cavalheiro, Alberto J. [UNESP]; Hyslop, Stephen; Puebla, Pilar; Feliciano, Arturo S.; Oshima-Franco, Yoko (Bentham Science Publishers, 2016)
Background: Of the various biological activities ascribed to extracts from Casearia sylvestris (guaï¿½atonga), its facilitatory activity, i.e., ability to increase skeletal muscle contractile amplitude, has promising therapeutic applications. In this work, we investigated the components responsible for the previously described neurofacilitation caused by C. sylvestris leaves. Methods: The methanolic fraction of C. sylvestris leaves was initially fractionated by column chromatography and partitioned in a MeOH:H2O gradient. The resulting fractions were analyzed by analytical HPLC and yielded fraction 5:5 (F55) that was subjected to solid phase extraction and preparative HPLC. Of the seven resulting subfractions, only F55-6 caused muscle facilitation. Subfractions F55-6 and F55-7 (similar in composition to F55-6 by TLC analysis, but inactive) were analyzed by 1H-NMR to identify their constituents. Results: This analysis identified a rutin-glycoside phytocomplex that caused neurofacilitation, a property that commercial rutin alone did not exhibit. Conclusion: F55-6 apparently caused neurofacilitation by the same mechanism (presynaptic action) as the methanolic fraction since its activity was also inhibited in tetrodotoxin-pretreated preparations.
Keywords: 1H-NMR; Chromatographic techniques; Facilitatory effect; Flavonoid glycosides; Guaï¿½atonga; Neuromuscular junction